Common framework on market-oriented agricultural advisory services - Chipeta, S.; Christoplos, I.; Katz, E. (CTA / NARO / Neuchâtel Group, 2008)
Produced with the Neuchâtel Group, an informal group of representatives of development agencies and professional institutions involved in agricultural development in sub-Saharan Africa, this booklet summarises the findings of more than 30 case-studies collected in 2006 on agricultural advisory services. It provides guidance on how to promote market orientation.